1998
DOI: 10.1017/s0950268898008905
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal trends of viral respiratory tract infections in the tropics

Abstract: To evaluate the seasonal trends of viral respiratory tract infections in a tropical environment, a retrospective survey of laboratory virus isolation, serology and immunofluorescence microscopy in two large general hospitals in Singapore between September 1990 and September 1994 was carried out. Respiratory tract viral outbreaks, particularly among infants who required hospitalization, were found to be associated mainly with respiratory syncytial (RSV) infections (72%), influenza (11%) and parainfluenza viruse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
250
7
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(288 citation statements)
references
References 28 publications
27
250
7
4
Order By: Relevance
“…In tropical settings lower respiratory infections in children are generally found to be more common during periods of higher rainfall and humidity, consistent with our results [7][8][9][10][11] . Rainfall is not convincingly associated with pneumonia incidence in time series studies from temperate settings 10,12,13 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In tropical settings lower respiratory infections in children are generally found to be more common during periods of higher rainfall and humidity, consistent with our results [7][8][9][10][11] . Rainfall is not convincingly associated with pneumonia incidence in time series studies from temperate settings 10,12,13 .…”
Section: Discussionsupporting
confidence: 92%
“…Low sunlight and temperature are consistently associated with high pneumonia incidence in time series studies in temperate settings, where annual peaks of lower respiratory infections occur during the short days of winter 10,[12][13][14][15][16] . The association between temperature and respiratory infections in children is inconsistent in time series studies from tropical settings, suggesting temperature is unlikely to be an important driver of pneumonia incidence in the tropics [6][7][8][9][10][11] . Less evidence examining the association of respiratory infection and sunlight exists from tropical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the northeast of England, a hospital-based study of the epidemiology of respiratory infections among pediatric inpatients over a six-year period showed that HPIV-1 and HPIV-2 epidemics occurred together, but only every 2 years [12]. In tropical countries, there have been fewer studies of HPIV and most of them do not demonstrate a seasonal pattern of HPIV infections [13,14].The purposes of the study were: (1) To determine the rate of HPIV infections among children attended at the Albert Sabin Children's Hospital (HIAS) over six consecutive years; (2) To describe the clinical and epidemiological characteristics of these infections; (3) To show the seasonal pattern of HPIV infections and its relation with the rainy season and with periods of activity of other respiratory viruses; and (4) To compare the clinical characteristics of parainfluenza infections with infections caused by respiratory syncytial virus (RSV), influenza and adenovirus. …”
mentioning
confidence: 99%
“…In the northeast of England, a hospital-based study of the epidemiology of respiratory infections among pediatric inpatients over a six-year period showed that HPIV-1 and HPIV-2 epidemics occurred together, but only every 2 years [12]. In tropical countries, there have been fewer studies of HPIV and most of them do not demonstrate a seasonal pattern of HPIV infections [13,14].…”
mentioning
confidence: 99%